Molecular codes defining rostrocaudal domains in the embryonic mouse hypothalamus - Ferran, José L.; Puelles, Luis; Rubenstein, John L. R. (Frontiers in Neuroanatomy, 2015)
The prosomeric model proposes that the hypothalamus is a rostral forebrain entity, placed ventral to the telencephalon and rostral to the diencephalon. Gene expression markers differentially label molecularly distinct dorsoventral progenitor domains, which represent continuous longitudinal bands across the hypothalamic alar and basal regions. There is also circumstantial support for a rostrocaudal subdivision of the hypothalamus into transverse peduncular (caudal) and terminal (rostral) territories (PHy, THy). In addition, there is evidence for a specialized acroterminal domain at the rostral midline of the terminal hypothalamus (ATD). The PHy and THy transverse structural units are presently held to form part of two hypothalamo-telencephalic prosomeres (hp1 and hp2, respectively), which end dorsally at the telencephalic septocommissural roof. PHy and THy have distinct adult nuclei, at all dorsoventral levels. Here we report the results of data mining from the Allen Developing Mouse Brain Atlas database, looking for genes expressed differentially in the PHy, Thy, and ATD regions of the hypothalamus at several developmental stages. This search allowed us to identify additional molecular evidence supporting the postulated fundamental rostrocaudal bipartition of the mouse hypothalamus into the PHy and THy, and also corroborated molecularly the singularity of the ATD. A number of markers were expressed in Thy (Fgf15, Gsc, Nkx6.2, Otx1, Zic1/5), but were absent in PHy, while other genes showed the converse pattern (Erbb4, Irx1/3/5, Lmo4, Mfap4, Plagl1, Pmch). We also identified markers that selectively label the ATD (Fgf8/10/18, Otx2, Pomc, Rax, Six6). On the whole, these data help to explain why, irrespective of the observed continuity of all dorsoventral molecular hypothalamic subdivisions across PHy and THy, different nuclear structures originate within each of these two domains, and also why singular structures arise at the ATD, e.g., the suprachiasmatic nuclei, the arcuate nucleus, the median eminence and the neurohypophysis.